Pelaksanaan Supervisi Klinis Sebagai Upaya Meningkatkan Aktivitas Guru Dalam Mewujudkan Pembelajaran Berkualitas Di Sekolah Dasar Binaan Kota Lhokseumawe Tahun 2021 - Sakdiah (Journal of Technology and Literacy in Education, 2022)
This study aims to determine the increase in teacher activity in realizing quality learning through the implementation of clinical supervision at the target elementary school in Lhokseumawe City in 2021. The location for this research is SD Negeri 16 Banda Sakti, SD Negeri 20 Banda Sakti, SD Negeri 1 Muara Dua, SD Negeri 1 Muara Dua, SD Negeri 20 Banda Sakti. Negeri 4 Muara Dua, SD Negeri 12 Muara Dua, SD Negeri 6 Muara Satu, SD Negeri 4 Blang Mangat, SD Negeri 13 Blang Mangat, SDS IT Bunayya Banda Sakti and SD Al-Quran Ar-Raudhah Blang Mangat. This research will be carried out for approximately 4 months, starting from July to October 2021. The subjects of this research were teachers in schools assisted by researchers who had not carried out optimal quality learning activities, namely 20 teachers. The procedure for implementing this research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection stages. Data collection was obtained from the results of observations. The analysis technique used in this research is descriptive qualitative. The results showed that in the first cycle of only 20 teachers who were subjects, only 9 teachers got good criteria, while 11 teachers got sufficient criteria with an overall average score of 80.55%. Whereas in cycle II all teachers have achieved indicators of research success, of the 20 teachers who were subjects, 12 teachers got good criteria, and 8 teachers got very good criteria with an overall average score of 89.38% and experienced an increase of 8 .83% when compared to cycle I. So it can be concluded that through the implementation of clinical supervision it can increase teacher activity in realizing quality learning in Lhokseumawe City Fostered Elementary Schools in 2021.